The effectiveness of the guided inquiry activity with the acid-base titration module on the high school student learning outcomes - Nurhayati Nurhayati; Iryani Iryani (Jurnal Pijar Mipa, 2022)
The study aims to reveal the effectiveness of guided inquiry activity-based acid-base titration modules on student learning outcomes in class XI MIPA SMA Negeri 2 Batang Anai, Padang, Indonesia. The population is the research sample selected using the purposive sampling technique, where 37 students as research subjects. The research instrument used was a learning outcome test in the form of multiple-choice questions, consisting of a pretest and a posttest. The average value of the increase in student learning outcomes in the subject class is 63.13. Subject class data were normally distributed and homogeneous. The results of the t-test are count (4.18) > table (1.9). The value of N-gain in the subject class is 0.72. The results showed that using the guided inquiry-based acid-base titration module effectively improved student learning outcomes.